Hidden Gems in the Wikipedia Discussions: The Wikipedians’ Rationales - Xiao, Lu (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
This paper presents a series of completed and ongoing studies that are aimed at understanding the role of the Wikipedians’ rationales in the Wikipedia discussions. We define a rationale as one’s justification of her viewpoint and suggestion. Our studies demonstrate the potential of leveraging the Wikipedians’ rationales in the discussions as resources for future decision-makings and as resources for eliciting knowledge about the community’s norms, practices and policies. Viewed as the rich digital traces in these environments, we consider them to be beneficial for the community members, such as helping newcomers familiarize themselves on the commonly accepted justificatory reasoning styles. We call for more research attention to the discussion content from this rationale study perspective.